Enhanced Osseointegration by the Hierarchical Micro-Nano Topography on Selective Laser Melting Ti-6Al-4V Dental Implants - Shu, Tianyu; Zhang, Yuchen; Sun, Guo; Pan, Yang; He, Gang; Cheng, Yilong; Li, Ang; Pei, Dandan (Frontiers in Bioengineering and Biotechnology, 2021)
Currently, selective laser melting (SLM) has been thriving in implant dentistry for on-demand fabricating dental implants. Based on the coarse microtopography of SLM titanium surfaces, constructing nanostructure to form the hierarchical micro-nano topography is effective in enhancing osseointegration. Given that current nanomodification techniques of SLM implants, such as anodization and hydrothermal treatment, are facing the inadequacy in costly specific apparatus and reagents, there has been no recognized nanomodified SLM dental implants. The present study aimed to construct hierarchical micro-nano topography on self-made SLM dental implants by a simple and safe inorganic chemical oxidation, and to evaluate its contribution on osteoblastic cells bioactivity and osseointegration. The surface chemical and physical parameters were characterized by FE-SEM, EDS, profilometer, AFM, and contact angle meter. The alteration on bioactivity of MG-63 human osteoblastic cells were detected by qRT-PCR. Then the osseointegration was assessed by implanting implants on the femur condyle of New Zealand Rabbits. The hierarchical micro-nano topography was constituted by the microrough surface of SLM implants and nanoneedles (diameter: 20~50 nm, height: 150~250 nm), after nanomodifying SLM implants in 30% hydrogen peroxide and 30% hydrochloride acid (volume ratio 1:2.5) at room temperature for 36 hours. Low chemical impurities content and high hydrophilicity were observed in the nanomodified group. Cell experiments on the nanomodified group showed higher expression of mitophagy related gene (PINK1, PARKIN, LC3B, and LAMP1) at 5 days and higher expression of osteogenesis related gene (Runx2 and OCN) at 14 days. In the early stage of bone formation, the nanomodified SLM implants demonstrated higher bone-to-implant contact. Intriguingly, the initial bone-to-implant contact of nanomodified SLM implants consisted of more mineralized bone with less immature osteoid. After the cessation of bone formation, the bone-to-implant contact of nanomodified SLM implants was equal to untreated SLM implants and marketable TixOs implants. The overall findings indicated that the inorganic chemical oxidized hierarchical micro-nano topography could enhance the bioactivity of osteoblastic cells, and consequently promote the peri-implant bone formation and mineralization of SLM dental implants. This study sheds some light on improvements in additive manufactured dental implants.